Hypoxia Promotes the Inflammatory Response and Stemness Features in Visceral Fat Stem Cells From Obese Subjects. Issue 3 (March 2016) - Petrangeli, Elisa; Coroniti, Giuseppe; Brini, Anna T.; de Girolamo, Laura; Stanco, Deborah; Niada, Stefania; Silecchia, Gianfranco; Morgante, Emanuela; Lubrano, Carla; Russo, Matteo A.; Salvatori, Luisa
Abstract : Low‐grade chronic inflammation is a salient feature of obesity and many associated disorders. This condition frequently occurs in central obesity and is connected to alterations of the visceral adipose tissue (AT) microenvironment. Understanding how obesity is related to inflammation may allow the development of therapeutics aimed at improving metabolic parameters in obese patients. To achieve this aim, we compared the features of two subpopulations of adipose‐derived stem cells (ASC) isolated from both subcutaneous and visceral AT of obese patients with the features of two subpopulations of ASC from the same isolation sites of non‐obese individuals. In particular, the behavior of ASC of obese versus non‐obese subjects during hypoxia, which occurs in obese AT and is an inducer of the inflammatory response, was evaluated. Obesity deeply influenced ASC from visceral AT (obV‐ASC); these cells appeared to exhibit clearly distinguishable morphology and ultrastructure as well as reduced proliferation, clonogenicity and expression of stemness, differentiation and inflammation‐related genes. These cells also exhibited a deregulated response to hypoxia, which induced strong tissue‐specific NF‐kB activation and an NF‐kB‐mediated increase in inflammatory and fibrogenic responses. Moreover, obV‐ASC, which showed a less stem‐like phenotype, recovered stemness features after hypoxia. Our findings demonstrated the peculiar behavior of obV‐ASC, their influence on the obese visceral AT microenvironment and the therapeutic potential of NF‐kB inhibitors. These novel findings suggest that the deregulated hyper‐responsiveness to hypoxic stimulus of ASC from visceral AT of obese subjects may contribute via paracrine mechanisms to low‐grade chronic inflammation, which has been implicated in obesity‐related morbidity. J. Cell. Physiol. 231: 668–679, 2016. © 2015 Wiley Periodicals, Inc.